Influence of machining parameters on cutting performance and wear mechanisms of coated carbide tools - Fransnazoan Sitorus; Naqasya Asyrori Sidabutar; Ulfani Ikhwana Purba; Derlini Derlini; Sumawijaya Suyatno (Politeknik Negeri Lhokseumawe, 2026)
In coated carbide cutting tools, the coating layer functions as a solid lubricant that improves wear resistance and minimizes frictional and thermal effects during machining. This study investigates the influence of machining parameters on cutting performance and characterizes the coating material and WC/Co carbide substrate to better understand their relationship with tool wear behavior. The machining parameters were established through an experimental design that evaluated mechanical loading, thermal loading, and chemical interactions using microstructural analysis. The experimental design evaluated the effects of mechanical loading, thermal loading, and chemical interactions through wear and microstructural analysis. Under mechanical loading, machining of Al-6061 produced mild abrasive wear with flank wear (VB) of 0.07 mm, while AISI 1070 generated higher edge wear of 0.25 mm. Under thermal loading, a 20% increase in cutting speed resulted in VB of 0.10 mm for Al-6061, whereas a 20% reduction in cutting speed for AISI 1070 produced VB of 0.16 mm accompanied by plastic deformation. Chemical interaction analysis showed stable coating integrity without delamination during Al-6061 machining. In contrast, AISI 1070 machining caused partial diamond film loss and substrate exposure, with approximately 35% diamond film remaining after wear progression. The results indicate that tool wear behavior is mainly controlled by mechanical loading, while thermal and chemical effects remain secondary. Abrasive wear was identified as the dominant wear mechanism, causing progressive coating removal without catastrophic delamination.